E-067 Balloon assisted Pre-operative Embolization of Hypervascular Metastatic Lesions to the Spine. (26th July 2014) - Jagadeesan, B; Mortazavi, S; Moen, S; Grande, A; Tummala, R
Abstract : Introduction: It is common to perform pre-operative embolization of metastatic lesions to the spine from hyper-vascular tumors. Typically, a microcatheter is navigated into a prominent arterial feeder to the tumor arising from a segmental artery or bronchial artery. Thereafter, particles or liquid embolic agents are injected into the tumor through the microcatheter, while taking care to avoid reflux into the proximal segmental artery or the aorta. However, occasionally, there may be a diffuse network of small arterial feeders arising from the segmental artery, which supply the tumor. None of these small arteries maybe amenable to selective catheterization, and embolization may be challenging due to the risk of reflux of embolic agent into the parent artery or aorta. Herein, we report our experience with embolising such metastatic lesions by injecting particles through a dual lumen balloon microcatheter positioned within the main segmental artery and using the inflated balloon to prevent reflux into the aorta. Materials and methods: We performed pre-operative embolization for hyper vascular vertebral metastases (two thoracic spine and 2 lumbar vertebrae) in a series of 3 patients (2 male and 1 female, mean age 53) with metastatic renal cell carcinoma at our institution using the 4 × 10 mm Sceptre C balloon microcatheter. In all patients, after ensuring that there was no radiculomedullary artery arising from the segmental artery supplying the tumor feeders, a 4 × 10 mm Sceptre C balloon microcatheter was navigated into the proximal aspect of the artery. The balloon was then inflated such that there was a tight seal across the origin of the artery from the aorta and embolization of the tumor was carried out with 150–300 microns PVA particles. Intermittently, the balloon was slowly deflated and DSA was carried out to assess changes in the tumor "blush". Embolization was carried out until there was elimination of the tumor blush. Results: The Sceptre C balloon microcatheter could be successfully navigated into the parent segmental vessel and inflated proximally across the origin of the vessel in all patients. Subsequent particle embolization resulted in complete elimination of the tumor "blush" in the vertebral body in every instance. There were no adverse events such as segmental arterial dissection, balloon rupture or reflux of particles into the aorta in any patient. Conclusion: Pre-operative embolization of hypervascular spinal mestastatic lesions can be safely carried out using a balloon-assisted technique with a dual lumen balloon microcatheter when traditional selective catheterization of feeder vessels is not feasible. Disclosures: B. Jagadeesan: None. S. Mortazavi: None. S. Moen: None. A. Grande: 2; C; Covidien, Integra. R. Tummala: 2; C; Lake Regional.